Systematic Analysis of Neurotransmitter Receptors in Human Breast Cancer Reveals a Strong Association With Outcome and Uncovers HTR6 as a Survival-Associated Gene Potentially Regulating the Immune Microenvironment - Zhang, Wei; Li, Lintai; Li, Jianxuan; Yu, Haiyan; Zheng, Fengping; Yan, Bin; Cai, Wanxia; Chen, Yumei; Yin, Lianghong; Tang, Donge; Xu, Yong; Dai, Yong (Frontiers in Immunology, 2022)
Many epidemiological reports have indicated an increase in the incidence of breast cancer among psychotic patients, suggesting that the targets of antipsychotics, neurotransmitter receptors, may have a role in tumorigenesis. However, the functions of neurotransmitter receptors in cancer are barely known. Here, we analyzed 44 neurotransmitter receptors in breast cancer and revealed that the expression of 34 receptors was positively correlated with relapse-free survival rates (RFS) of patients using the public database (n = 3951). Among all these receptors, we revealed decreased expression of HTR6 in human advanced breast cancer versus tumors in situ using our original data (n = 44). After a pan-cancer analysis including 22 cancers (n = 11262), we disclosed that HTR6 was expressed in 12 tumors and uncovered its influence on survival in seven tumors. Using multi-omics datasets from Linkedomics, we revealed a potential regulatory role of HTR6 in MAPK, JUN, and leukocyte-differentiation pathways through enriching 294 co-expressed phosphorylated proteins of HTR6. Furthermore, we proclaimed a close association of HTR6 expression with the immune microenvironment. Finally, we uncovered two possible reasons for HTR6 down-regulation in breast cancer, including deep deletion in the genome and the up-regulation of FOXA1 in breast cancer, which was a potential negatively regulatory transcription factor of HTR6. Taken together, we revealed a new function of neurotransmitter receptors in breast cancer and identified HTR6 as a survival-related gene potentially regulating the immune microenvironment. The findings in our study would improve our understanding of the pathogenesis of breast cancer and provided a theoretical basis for personalized medication in psychotic patients.